Efficacy of a commercial bacteriophage cocktail against planktonic cells and both thin and thick biofilms of skin pathogens, measured using isothermal microcalorimetry - Lafranca, Tecla; Bonkat, Gernot; Rieken, Malte; Braissant, Olivier (Frontiers in Microbiology, 2025)
IntroductionSkin and soft tissue infections are frequent and often require antibiotic treatment. However, for mild and self-limiting lesions, bacteriophage therapy could be an interesting treatment option that limits the use of antimicrobials and helps avoid the development of resistance. Still, very little is known about the efficacy of commercial phage cocktails against the biofilms encountered in these lesions. In this study, we investigated the use of a commercial phage cocktail against Staphylococci and Streptococci grown planktonically in thin and thick biofilms.MethodsIsothermal microcalorimetry was used to monitor the metabolic activity of planktonic cells, as well as cells grown in thin or thick biofilms of common skin pathogens (Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus agalactiae), when exposed to the commercial phage cocktail.ResultsThe use of phages against sensitive strains showed a rapid decrease in metabolic activity in planktonic cells. However, when applied to a thin biofilm, the effect was already less, although it was still important. Finally, no effect was visible on thick and mature biofilms.ConclusionThe efficacy of bacteriophage cocktails is limited by the thickness and maturation of biofilms. In the case of skin and soft tissue infections, especially for chronic wounds, it might be necessary to mechanically remove and disrupt the biofilm through mechanical debridement to enable the phage product to be effective.